2007
DOI: 10.1039/b607428f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and applications of superacids. 1,1,2,2-Tetrafluoroethanesulfonic acid, supported on silica

Abstract: In this paper we focus on the synthesis and use of superacids, in particular 1,1,2,2tetrafluoroethanesulfonic acid (TFESA), and describe how these can be optimized for reactions of key industrial importance. One area of considerable interest is the field of superacid catalysis and, specifically, the development of safer and more cost-effective acid catalysts. We report a new simplified route for preparation of these acids, making these more readily available and opening up a large number of opportunities. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 13 publications
(17 reference statements)
0
31
0
Order By: Relevance
“…PFS nanoparticles lost their acid groups to a larger extent than AS nanoparticles did. Fluoroalkyl-sulfonic acids have superacidic character but they are also water sensitive [17,42,43,51]. The anchorage of PFS acids on SiMNPs was not enough to improve its stability.…”
Section: Cellobiose Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…PFS nanoparticles lost their acid groups to a larger extent than AS nanoparticles did. Fluoroalkyl-sulfonic acids have superacidic character but they are also water sensitive [17,42,43,51]. The anchorage of PFS acids on SiMNPs was not enough to improve its stability.…”
Section: Cellobiose Hydrolysismentioning
confidence: 99%
“…Nanoporous solids with acid sites have shown high catalytic activity in gas and liquid phase reactions [17]. Efficient catalysis of cellulose hydrolysis was observed using amorphous carbon with surface sulfonic acid, carboxylic acid, and hydroxyl groups [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is categorized as a superacid and expected to be an effective catalyst for Friedel-Crafts C-acylation. A comparative study using sulfuric acid, TfOH, and three other perfluorinated sulfonic acids synthesized by Harmer et al [15] in the acylation of anisole 1 (Figure 2a) proved this expectation. Moreover, the Fries rearrangement of phenyl acetate 2 ( Figure 2b) also shows high efficiency of TfOH utilization as a catalyst as it is 100 times stronger than sulfuric acid [13,16] and is a commercially available reagent which can be readily used for these reactions.…”
Section: General Features Of the Tfoh Catalytic System For C-acylationmentioning
confidence: 72%
“…Harmer et al 29 have applied the sol-gel technique to prepare 1,1,2,2-tetrafluoroethanesulfonic acid supported on silica, which proved to be an excellent catalyst for several processes such as alkylation and acylation of aromatics, isomerization, oligomerization, and Fries rearrangement. This material has activity similar to that of triflic acid but is much easier to handle.…”
Section: Immobilized Superacids (Bound To Inert Supports)mentioning
confidence: 99%
“…Harmer et al 28,29 have reported the synthesis of 1,1,2,2-tetrafluoroethanesulfonic acid, CF 2 HCF 2 SO 3 H, and 1,1,2,3,3,3-hexafluoropropanesulfonic acid, CF 3 CFHCF 2 -SO 3 H, by the addition of sulfite to fluorinated double bonds [Eq. (2.12)].…”
mentioning
confidence: 99%